Multiple Abscess Collections: Antibiotics or Steroids? - Philippe Raphael Dias; Levin Bolt; Christof Iking-Konert; Mattia Arrigo; Lars C. Huber (Case Reports in Immunology)
Aseptic abscess syndrome (AAS) is a medical rarity. The combination of multiple abscess collections in different organs, negative microbiological studies, and the association with an inflammatory bowel disease is highly suggestive for an AAS. The AAS is an acute neutrophilic dermatosis, so “generalized pyoderma gangraenosum” or “generalized bullous sweet syndrome” might be used synonymously. It is important to note that the diagnosis of an AAS can be made only after careful exclusion of an infectious disease. Of interest, despite the severity of the inflammation, patients with AAS are commonly hemodynamically stable. To date, no studies have investigated the optimal regimen, dose, and duration of therapy. Corticosteroids are the cornerstone of immunosuppression during the acute phase. After the induction phase, therapy might be switched to anakinra or infliximab.